Symbolic Interaction and Applied Social Research: A FOCUS ON TRANSLATIONAL SCIENCE RESEARCH(1) - Kotarba, Joseph A. (2014)
In symbolic interaction, a traditional yet unfortunate and unnecessary distinction has been made between basic and applied research. The argument has been made that basic research is intended to generate new knowledge, whereas applied research is intended to apply knowledge to the solution of practical (social and organizational) problems. I will argue that the distinction between basic and applied research in symbolic interaction is outdated and dysfunctional. The masters of symbolic interactionist thought have left us a proud legacy of shaping their scholarly thinking and inquiry in response to and in light of practical issues of the day (e.g., Znaniecki, and Blumer). Current interactionist work continues this tradition in topical areas such as social justice studies. Applied research, especially in term of evaluation and needs assessment studies, can be designed to serve both basic and applied goals. Symbolic interaction provides three great resources to do this. The first is its orientation to dynamic sensitizing concepts that direct research and ask questions instead of supplying a priori and often impractical answers. The second is its orientation to qualitative methods, and appreciation for the logic of grounded theory. The third is interactionism’s overall holistic approach to interfacing with the everyday life world. The primary illustrative case here is the qualitative component of the evaluation of an NIH-funded, translational medical research program. The qualitative component has provided interactionist-inspired insights into translational research, such as examining cultural change in medical research in terms of changes in the form and content of formal and informal discourse among scientists; delineating the impact of significant symbols such as "my lab" on the social organization of science; and appreciating the essence of the self-concept "scientist" on the increasingly bureaucratic and administrative identities of medical researchers. This component has also contributed to the basic social scientific literature on complex organizations and the self.